Technical Demography - Ramakumar, R.; Gopal, Y.S. (New Delhi: New Age, 2006)
Technical Demography provides a comprehensive introduction to the measurement and analysis of demographic data. It emphasizes the application of mathematical and statistical methods in demographic studies, offering a systematic approach to understanding population dynamics. The book is designed to cater to students, researchers, and professionals interested in the quantitative aspects of demography.
Includes index and bibliography
Keywords: Demographic Surveys; Mathematical Models; Demography